PRICE PERCEPTION AND PROMOTION ANALYSIS OF PURCHASING DECISIONS ON ONLINE TRAVEL APPS - Enny Diah Astuti; Nika Sintesa; Widiarti Lestariningsih (Yayasan Education and Social Center, 2023)
This study aims to determine and analyze price perceptions and promotions of simultaneous purchasing decisions for online travel application customers. The type of research used is explanatory research. The research will explain the relationship between research variables by testing hypotheses that researchers have developed to explain the relationship between price perception variables and promotion variables to purchasing decisions in online travel applications. To present research results of a numerical nature, including numbers to describe and explain phenomena that reflect research results. The study showed a relationship between the promotion and purchase decision variables. Suppose the quantity r or Pearson correlation in this analysis is positive. In that case, the relationship between the two variables is positive, or in other words, increased price awareness and promotion will also improve purchasing decisions. Price perception and promotion research on purchasing decisions can use as a reference source for management to maintain quality service. The prices and promotions offered and attractive features can continue to develop to support application users so that consumer satisfaction achieve in purchasing decisions.